Case Studies on the Implementation of Lean Manufacturing in the Automotive Malaysian Companies - Mohd Azhar, Sahwan; Mohd Nizam A., Rahman; Baba, M. Deros (Trans Tech Publications Inc., 2014)
Lean manufacturing is one of the initiatives that many major businesses in the world have been trying to adopt in order to remain competitive in an increasingly global market. The focus of the approach is on cost reduction by eliminating non-value added activities. Originating from the Toyota Production System, many of the tools and techniques of lean manufacturing have been widely used in discrete manufacturing. The purpose of this study is to investigate the approach of adopting lean, the tools and techniques implemented, the changes in the organizations, the problems encountered as well as the lessons learnt. This paper describes the results and findings of four industrial case studies conducted in different electrical and electronics companies in Malaysia. Interviews were conducted with the key personnel to answer some issues which were crucial in this study. Comparisons and discussion were made among the case companies. One of the key findings obtained is that people in the organization should take the lean mind-set and act in the lean way in order to make a lean initiative successful. The application of kaizen and 7 quality control tools are most popular implementation in the selected case study companies as the tools to eliminate non-value added activities.